Penggunaan Media Caps Scrapbook Untuk Meningkatkan Motivasi Belajar Peserta Didik Dalam Pembelajaran Fikih Materi Sedekah Kelas 5 SD/MI - Agustin Arianti Uswatun Kasanah; Siswi Jayanti; Asnal Mala (JURNAL PENDIDIKAN & PENGAJARAN (JUPE2), 2025)
This research explains how Scrapbook learning media is used to increase students' learning motivation in learning fiqh for grade 5 students in SD / MI. The method used in this research is literature study. The conclusion in this study is the use of learning media Caps Scrapbook to increase student learning motivation in learning fiqh grade 5 SD / MI can be concluded that with the use of learning media Caps Scrapbook can increase student learning motivation, in addition to increasing learning motivation in students can also make students become more active in learning. Caps Scrapbook learning media is one alternative that can be used as a learning media that is not only fun but also effective. Caps Scrapbook is a flexible learning media because it can be applied in any subject and at any level. The conclusion of the research is proven from various results of other people's research that has been done before.